Future Direction of Binding Sale-Purchase Agreements as Tax Objects for Land and Building Rights Acquisition - Keumala, Dinda; Probondaru, Ignatius Pradipa; Setiawati, Anda; Arsawan, I Gede Yudi; Wiratno, Wiratno (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
A Binding Sale and Purchase Agreement is a preliminary agreement made by parties before a Notary before the execution of a Sale and Purchase Deed before the Land Deed Official. This study examines the existence of a binding sale and purchase agreement regulation as the object of the Levy on Acquisition of Land and Building Rights payment, it identifies the factors causing inconsistencies in the normative regulation of A Binding Sale and Purchase Agreement transaction as the Levy on Acquisition of Land and Building Rights objects. The findings show that there are inconsistencies between the provisions stipulated in Law No. 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments and Government Regulation No. 35 of 2023 concerning General Provisions for Regional Taxes and Regional Levies regarding the timing and object of the Levy on Acquisition of Land and Building Rights payment. Specifically, Article 49 letter a of Law No. 1 of 2022 determines that the Levy on Acquisition of Land and Building Rights is due at the signing of the binding Sale and Purchase Agreement, while Article 18 paragraph (3) of Government Regulation No. 35 of 2023 stipulates different conditions, leading to regulatory disharmony.